Editorial: Scientific Writing Workshop on TELKOMNIKA Editors and Authors Meeting (TEAM) - Tole Sutikno (Universitas Ahmad Dahlan, 2018)
In this year, TELKOMNIKA is organizing scientific writing workshop series for improving manuscript quality which is called as “Scientific Writing Workshop on TELKOMNIKA Editors and Authors Meeting (TEAM)”. This workshop is aimed at developing scientific writing skills to both editing and proofreading for preparing final manuscript. Editing covers reread manuscript which includes content, overall structure, clarity, style and citations to see whether the manuscript is well-organized and the transitions between paragraphs are smooth. Proofreading is the final stage of the editing process, focusing on surface errors such as misspellings and mistakes in grammar and punctuation. This process is just as important as any other aspect of writing. The process is instrumental in getting ideas across in an accessible and logical manner.